Historical sources of black carbon identified by PAHs and δ13C in Sanjiang Plain of Northeastern China. (May 2018) - Gao, Chuanyu; Liu, Hanxiang; Cong, Jinxin; Han, Dongxue; Zhao, Winston; Lin, Qianxin; Wang, Guoping
Abstract: Black carbon (BC), the byproduct of incomplete combustion of fossil fuels and biomass can be stored in soil for a long time and potentially archive changes in natural and human activities. Increasing amounts of BC has been produced from human activities during the past 150 years and has influenced global climate change and carbon cycle. Identifying historical BC sources is important in knowing how historical human activities influenced BC and BC transportation processes in the atmosphere. In this study, PAH components and δ 13 C-BC in peatland in the Sanjiang Plain were used for identifying and verifying regional BC sources during the last 150 years. Results showed that environment-unfriendly industry developed at the end of the 1950s produced a great amount of BC and contributed the most BC in this period. In other periods, however, BC in the Sanjiang Plain was mainly produced from incomplete biomass burning before the 1990s; particularly, slash-and-burn of pastures and forests during regional reclamation periods between the 1960s and 1980s produced a huge amount of biomass burning BC, which then deposited into the surrounding ecosystems. With the regional reclamation decreasing and environment-friendly industry developing, the proportion of BC emitted and deposited from transportation sources increased and transportation source became an important BC source in the Sanjiang Plain after the 1990s. Graphical abstract: Image 1 Highlights: Historical black carbon (BC) sources in Sanjiang Plain (China) are quantified. First research of tracking historical BC sources through PAHs and δ 13 C-BC. Proportions of BC from biomass burning were decreased gradually before the 1950s. Industry developing and reclamation were the major BC sources around the 1960s. Transportation sources became the major BC sources after the 1990s.